2021
DOI: 10.7554/elife.60100
|View full text |Cite
|
Sign up to set email alerts
|

Sequential perturbations to mouse corticogenesis following in utero maternal immune activation

Abstract: In utero exposure to maternal immune activation (MIA) is an environmental risk factor for neurodevelopmental and neuropsychiatric disorders. Animal models provide an opportunity to identify mechanisms driving neuropathology associated with MIA. We performed time course transcriptional profiling of mouse cortical development following induced MIA via poly(I:C) injection at E12.5. MIA-driven transcriptional changes were validated via protein analysis, and parallel perturbations to cortical neuroanatomy were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 88 publications
1
29
1
Order By: Relevance
“…Interestingly, Choi et al found that poly (I:C)-induced MIA and IL-17A administration to the embryonic brain on E14.5 resulted in patch-like cortical dysplasia on E18.5 (25), which is similar to some human patients with ASD (30). Their group reproduced the results by another study (31); however, another group mentioned that they could not find any patches after MIA; therefore, the occurrence of cortical patches remains controversial (32).…”
Section: Relationship Between Il-17 Exposure and Asd In The Rodent Em...mentioning
confidence: 86%
“…Interestingly, Choi et al found that poly (I:C)-induced MIA and IL-17A administration to the embryonic brain on E14.5 resulted in patch-like cortical dysplasia on E18.5 (25), which is similar to some human patients with ASD (30). Their group reproduced the results by another study (31); however, another group mentioned that they could not find any patches after MIA; therefore, the occurrence of cortical patches remains controversial (32).…”
Section: Relationship Between Il-17 Exposure and Asd In The Rodent Em...mentioning
confidence: 86%
“…In another ASD model of maternal immune activation (MIA), we found that klf7 was upregulated at E17.5 and downregulated at P0 [ 55 ]. Epidemiological evidence is growing that environmental exposure early in development has an impact on ASD susceptibility later in life [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…OPEN ACCESS radial migration, and cell type composition in the cortex. These alterations have long-lasting effects on brain functional maturation and animal behavior [29,59,60]. Cortical GABAergic neurons reportedly exhibit specific vulnerability to environmental insults [59,61].…”
Section: Trends In Neurosciencesmentioning
confidence: 99%